Faktor yang Mempengaruhi Keberkesanan Pemilihan Projek Sistem Maklumat - Syaifudin (2011)
The effectiveness of an information system (IS) project selection is measured by the success of the project and the expected impact. An information system project is difficult to select due to many factors that influence it, which leads to the possibility of fail to perform. Among the possible reasons are lack of consideration to the user involvement and acceptance, and the organizational capability to innovate. In Indonesia these problems are look similar almost in every state. The lack of model in selecting the project has initiated the idea to conduct this research. The objective of this study is to develop a model that is more effective to use in making decision during the IS project selection process. Based on literatures and existing theories, the theoretical framework or model of research is proposed, which consists of exogenous and endogenous variables. The exogenous variables are technology, economy and environment, while endogenous variables are user acceptance, organizational capability and effectiveness of information system project selection. Data are collected from Bureau Planning, and Data and Information Center for each ministry in the Indonesian government. Out of 294 questionnaires completed only 263 were usable for further analysis using Structural Equation Modeling (SEM). From the analysis, it found that technology has direct effect on the information system project selection while user acceptance and organizational capability directly influence the project selection. Furthermore, economics and environment factors directly affect the user acceptance. As a conclusion, this research has proposed four models and revealed that the technology factor is the most dominant factor that influence to the information system project selection. The contribution of the research is not only could identified the dominant factor or variable for IS project selection process, but also could guide decision makers to make decision based on those proposed models. This research ends with the suggestion for the industry, discusses the limitations of the study and gives some suggestions for future research.